Transformation of Khataman Al-Qur'an in The Pandemic Time of Covid-19 - May Salwa Billah Safirah; Agus Machfud Fauzi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
Khataman Al-Quran is the activity of reading Al-Quran which starts from surah al-Fatihah to surah an-Naas. Khataman Al-Quran is one of the religious activities carried out by Fatayat Muslimat NU (Nahdatul Ulama) Sarirejo. Khataman Al-Quran can transform when its implementation is disturbed. As was the case when there was a covid-19 pandemic outbreak, all forms of religious activities of the NU Muslim Fatayat underwent a transformation. The purpose of this study was to analyze the transformation of the Khataman Al-Quran carried out by Fatayat Muslimat NU during the Covid-19 pandemic. Researchers used qualitative methods because, in accordance with the research discussion, the results could not be measured by NUmbers but by using words. The data collection techniques used were observation and in-depth interviews. The theory used in this research is Talcott Parson's AGIL theory. There are 4 things that are interconnected, namely adaptation, goal attainment, integration, and latency. The result of this research is that the Khataman al-Qur'an carried out by Fatayat Muslimat NU in Sarirejo District underwent a transformation during the Covid-19 pandemic. The transformation that occurred was the change in reading the khataman Al-Quran face-to-face in Sarirejo Subdistrict to face-to-face reading in each village and being guided online by the Fatayat Muslimat NU, Sarirejo District. The transformation occurred because there were restrictions on community activities in order to stop the spread of covid-19.